ChemInform Abstract: An Efficient and Tunable Route to Bis(1, 2, 3‐triazol‐1‐yl)methane‐Based Nitrogen Compounds. Issue 25 (June 2016) - Castro‐Osma, Jose A.; Lara‐Sanchez, Agustin; Otero, Antonio; Rodriguez, Ana M.; de la Torre, Maria C.; Sierra, Miguel A.
Abstract: 1, 3‐Dipolar cycloaddition of geminal diazides with alkynes provides the title species (III) and (V).